(untitled) (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
This study examines the housing needs and population growth dynamics in Campaka Sub-district, Purwakarta Regency, Indonesia, an area characterized by rapid industrial expansion. The research applies the share of growth method to compare population growth between Campaka and Purwakarta Regency, revealing a consistently upward trend in Campaka’s demographic growth. Findings indicate a substantial gap between available housing supply and projected demand, with approximately 14,434 housing units estimated to be required by 2030. This demand can be met with a surplus of supply, which stimulates in-migration and accelerates the residential development. The analysis highlights the risks of unbalanced development when industrial growth outpaced housing provision, potentially leading to urban challenges such as overcrowding and infrastructure strain. The study recommends adopting a cautious approach to residential development, emphasizing the need for close monitoring of industrial activities and flexible adjustment of housing permits. Furthermore, active participation of local stakeholders in the planning process is considered crucial to ensure that housing policies align with community needs and long-term regional development objectives.